2021
DOI: 10.1002/ajoc.202100511
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst‐Free Hydrogen Proton Transfer Reduction of Nitrobenzamides to Aminobenzamides with iPrOH/KOH System

Abstract: A reduction of nitrobenzenes via the combination of KOH and isopropanol was established for the general synthesis of aniline derivatives. A metal catalyst isn't required in this alternative reduction reaction, and a series of nitrobenzamide compounds were chemoselectively reduced into the corresponding aminobenzamides in good to excellent yields. This reaction is operationally simple, and proceeds under mild conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 41 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…When ethanolamine is used in this setting, it is likely that intermediate II is rapidly deoxygenated precluding formation of a Michael acceptor species (III) and subsequent incorporation of the alkoxy group into the sidechain. [24] Further work to delineate this deoxygenation process is currently ongoing in our laboratory.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When ethanolamine is used in this setting, it is likely that intermediate II is rapidly deoxygenated precluding formation of a Michael acceptor species (III) and subsequent incorporation of the alkoxy group into the sidechain. [24] Further work to delineate this deoxygenation process is currently ongoing in our laboratory.…”
Section: Resultsmentioning
confidence: 99%
“…In the absence of a carbonyl group (as in 1 x ) the intermediate corresponding to II cannot be deprotonated at the α‐position and the hydroxyindazole 3 x is obtained as the main reaction product. When ethanolamine is used in this setting, it is likely that intermediate II is rapidly deoxygenated precluding formation of a Michael acceptor species ( III ) and subsequent incorporation of the alkoxy group into the side‐chain [24] . Further work to delineate this deoxygenation process is currently ongoing in our laboratory.…”
Section: Resultsmentioning
confidence: 99%
“…1 H NMR (500 MHz, CDCl3): δ 6.79 (t, J = 8.9 Hz, 1H), 6.47−6.35 (m, 2H), 3.92−3.81 (t, 4H), 3.57 (s, 2H), 3.03− 2.91 (t, 4H). 13 (40). 70 It is obtained as a colorless liquid (45.21 mg, 95%) after purification by column chromatography (n-hexane/EtOAc: 90:10).…”
Section: ■ Conclusionmentioning
confidence: 99%
“…Although CTHs using isopropanol are well established, , , related reactions applying methanol is less explored. Nevertheless, in recent years, methanol has been emerging as an important reducing agent, and several research groups have shown significant interest in its utilization in organic transformations (Scheme ). For instance, Cu-catalyzed reduction of furfural and HMF is reported using MeOH .…”
Section: Introductionmentioning
confidence: 99%